2019
DOI: 10.1029/2019jf005094
|View full text |Cite
|
Sign up to set email alerts
|

Large Effects of Particle Size Heterogeneity on Dynamic Saltation Threshold

Abstract: Reliably predicting the geomorphology and climate of planetary bodies requires knowledge of the dynamic threshold wind shear velocity below which saltation transport ceases. Here we measure this threshold in a wind tunnel for four well‐sorted and two poorly sorted sand beds by visual means and by a method that exploits a regime shift in the behavior of the surface roughness caused by momentum transfer from the wind to the saltating particles. For our poorly sorted sands, we find that these measurement methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…All data shown in the figures of this review can be found in the following references: Peyneau and Roux (2008a Bagnold (1937), Chepil (1945), Ho (2012), Martin and Kok (2018), and Zhu et al (2019). We thank Michael Church and three anonymous reviewers for their critical reviews and numerous insightful comments and suggestions.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…All data shown in the figures of this review can be found in the following references: Peyneau and Roux (2008a Bagnold (1937), Chepil (1945), Ho (2012), Martin and Kok (2018), and Zhu et al (2019). We thank Michael Church and three anonymous reviewers for their critical reviews and numerous insightful comments and suggestions.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, it is unclear whether this is also true for sediment transport cessation. While the continuous rebound mechanism (see section 4.2) is clearly a size-selective process (coarser particles are less accelerated during their trajectories), impact entrainment may not be Zhu et al, 2019). Furthermore, in heterogeneous sediment beds, relatively…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%
See 3 more Smart Citations